Profile of chicken meat consumers in the city of Salgueiro - PE - Brazil (Research, Society and Development, 2022)
Brazil has great potential in the production of chicken meat and is a great international highlight in exports of this protein. Within the national agriculture, it is classified as one of the best consolidated activities, due to the precariousness of information on commercialization and local consumption of chicken meat, the present study aims to characterize consumption and consumer in the city of Salgueiro in the state of Pernambuco. The research took place in the municipality of Salgueiro-PE, the "survey" research method was used to collect the research information with the resolution of the questionnaire, the questionnaire was composed of open and closed questions and the interviewees were randomly selected at the purchase establishment. . A total of 364 questionnaires were applied from August 19 to 25, 2019. After data collection, they were destined and converted into an Excel spreadsheet, which after being sorted through the mathematical and comparative constructions, the results were presented in the form of tables and graphs. Subsequently, in the second stage, the data were submitted to correlation tests being described in graphs with the statistical software R Core Team (2022), to determine the relationship between dependence on variables. The present research shows a higher percentage of women interviewed (60.40%), and 26.11% of the interviewed public were aged between 20 and 25 years old, of the total number of interviewees 97.8% say they consume chicken meat, those who do not eat this protein say that the reason is because they believe in the use of hormones in the diet of chickens or simply because they do not enjoy this meat, 48.9% consume chicken protein daily, breast and thigh are the most popular cuts. consumed by the local community presented for both a percentage of consumption equal to 26.7% of the interviewees. It can be concluded that the municipality of Salgueiro-PE has potential for the commercial chicken meat market, since its consumption has shown to be quite expressive.